2014
DOI: 10.1155/2014/208408
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum RANTES Levels and the Severity of Parkinson’s Disease

Abstract: Inflammatory mediators may reflect a role of systemic inflammation in the neurodegenerative process of Parkinson's disease (PD). Interleukin-6 (IL-6) and chemokine ligand 5 (CCL5), also known as RANTES (regulated on activation, normal T cell expressed and secreted), have been implicated in neurodegenerative diseases including PD. Serum levels of RANTES and IL-6 of 78 consecutive PD patients and age-matched 80 controls were measured. Patients with PD had higher RANTES and IL-6 levels compared with the controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 21 publications
3
31
1
Order By: Relevance
“…12 Interestingly, the combination of TNF-a with the ratio of P-Tau/a-synuclein was that which best classified PD patients. Conversely, there were no differences in plasma IL-6 levels in PD patients and controls, in contrast to earlier studies that reported increases 13,14,[35][36][37] or decreases 38 in this parameter. However, the levels of IL-6 in PD patients apparently augment as the disease becomes more severe, both in terms of motor and nonmotor features, as shown by the positive correlations with the UPDRS scores I to III.…”
Section: E L G a D O -A L V A R A D O E T A Lcontrasting
confidence: 99%
“…12 Interestingly, the combination of TNF-a with the ratio of P-Tau/a-synuclein was that which best classified PD patients. Conversely, there were no differences in plasma IL-6 levels in PD patients and controls, in contrast to earlier studies that reported increases 13,14,[35][36][37] or decreases 38 in this parameter. However, the levels of IL-6 in PD patients apparently augment as the disease becomes more severe, both in terms of motor and nonmotor features, as shown by the positive correlations with the UPDRS scores I to III.…”
Section: E L G a D O -A L V A R A D O E T A Lcontrasting
confidence: 99%
“…Studies reporting increased serum RANTES levels in association with IL-15, IL-8, and MCP-1 in PD patients suggest that the dysregulation in the peripheral cytokine network might be related to the pathogenesis and underlying neurodegeneration [19, 27, 28]. In addition, RANTES serum levels were reported to correlate with disease severity [29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…The measured cytokines were selected based on the reported alterations in the C9orf72 knock-out murine model studies [1][2][3]. Additionally, RANTES and IL-8 were chosen based on assay availability and based on previous studies showing alterations in the peripheral levels of these cytokines especially in ALS and Parkinson's disease [22][23][24][25].…”
Section: Cytokine and Chemokine Analyses In Patients With Ftldmentioning
confidence: 99%